The role of ethnic identity in OC symptom dimensions among Asian Americans - Ching, Terence H.W. (J Obsessive Compuls Relat Disord, 2019)
Little is known about obsessive-compulsive (OC) symptoms in Asian Americans. Past research has shown elevations in certain symptom dimensions when compared with White Americans, but there have not been any studies on cultural mechanisms for these differences. In this study, we examined whether ethnic identity mediated differences in severity of various OC symptom dimensions between Asian and White Americans. A total of 453 participants (79 Asian American, 374 non-Hispanic White) completed measures of ethnic identity and OC symptoms. Separate boostrapped mediation analyses were conducted to determine the indirect (i.e., mediation) effect of ethnoracial group membership on different OC symptom dimensions, via ethnic identity. There was significant evidence of mediation across the majority of OC subscales examined. Asian Americans reported stronger ethnic identity than their White counterparts, which in turn predicted more severe contamination obsessions and washing compulsions, harm-related intrusions, checking, neutralizing, as well as symmetry/ordering symptoms. This study is the first to demonstrate an exacerbating function of ethnic identity for OC symptoms among Asian Americans, contrary to some previous evidence of its protective role for overall mental health among ethnoracial minorities. More research is needed to test and validate hypotheses about why ethnic identity mediated group differences in OC symptoms.